Bagaimana Sekolah Dasar Mengikuti Pedoman Teknis Internasional UNESCO dalam Menerapkan Pendidikan Seks? - Mahanani, Vioni Ilmi (Griya Widya: Journal of Sexual and Reproductive Health, 2023)
Purpose: The purpose of this study was to analyze the implementation of sex education at the Al Abidin International Islamic Elementary School (SDII) Al Abidin, identify the level of suitability of the implementation of sex education based on the UNESCO sex education guidelines, identify the obstacles faced by teachers when implementing sex education in schools. Method: This research uses a qualitative descriptive research type. The data analysis technique used interactive analysis. Result: (1) SDII Al Abidin in the sex education program invites parents to take part in the planning and implementation of school sex education. SDII Al Abidin implements sex education through a combination of fiqh material and school material which is internalized into the planning of the PreKBM program and the school's KBM period. (2) the sex education program at SDII Al Abidin as a whole has complied with the sex education guidelines by UNESCO, methods have not been fully implemented, such as: involving youth and community leaders in sexual education planning; not yet informed about the sexually transmitted disease HIV/AIDS; and have not demonstrated individual attitudes and norms with peers about condoms and various types of contraception (3) the obstacles experienced by SDII Al Abidin, namely: asynchronous communication between teachers and some parents and teachers lack confidence in managing language.